Indonesian Students’ Comprehension Of The French Articles (Les Articles): The Case Of Manado State University French Language Education Program - Sekeh, W E (Journal of Educational Method and Technology, 2019)
In French language, articles play an important role and one of the basic French skills is mastery of article usage. The objective of this study is to describe students’  performance and mastery of French articles. The research used descriptive research method. Data of the study were obtained by giving written tests of French language articles to French Language Education Program students enrolled in the 2018/2019 school year. The research instrument consisted of questions in the form of loose questions and questions in the form of text / short discourse. Data analysis used descriptive statistics analysis. Study result shows that students’ mastery of French article is quite low (Mean=48.28). However, there is difference in performance of each article type. Mastery of definite article is the highest (Mean=60.78)Keywords: definite article; indefinite article; partitive article; performance; mastery